Efektivitas Mobilisasi Saraf Nervus Ischiadicus pada Kasus Ischialgia Et Causa Sindroma Piriformis Setelah Diberikan Terapi Standar - Zuhri, Saifudin; Suwarni, Sri (Nur Science Institute, 2023)
Ischialgia ec piriformis syndrome is a disorder of the ischiadicus nerve in the form of pain radiating from the buttocks through the hamstrings to the feet. This case arises mainly due to shortening of the piriformis muscle so that it suppresses the sciatic nerve. Physiotherapy as a health worker plays a role in treating ischialgia cases where nerve mobilization technology in this case has not been widely implemented. The objectives of the study was to determine the effectiveness of nerve mobilization after being given standard therapy. Research subjects: Patients who were treated at Sunafa with complaints of ischialgia ec piriformis syndrome who met the study criteria. This study is experimental research in the form of a two group pre and post test design, place at Sunafa Physiotherapy practice from March to May 2023. Subjects were divided into 2 groups by lottery, namely group I as many as 18 research subjects received standard therapy treatment and nerve mobilization and group II as many as 17 research subjects received standard therapy treatment. VAS of both groups, namely initial and final VAS. In group I, the initial VAS averaged 68.61mm and the final VAS averaged 8.83mm. In group II, the initial VAS was 61.53 mm and the final VAS was 10.67 mm. Data analysis results shows that data normality test for group I initial VAS p=0.128 (p>0.05), final VAS p=0.04 (p<0.05), in group II initial VAS p=0.098 (p>0.05) and final VAS p=0.005 ( p<0.05). So the initial VAS data for the two groups were normally distributed and the final VAS data for the two groups were not normally distributed, so the data was tested non-parametric. The results of the data homogeneity test obtained p=0.049 (p<0.05) meaning that the data was not homogeneous. Group I Wilcoxon test obtained p=0.000 (p<0.001). Group II Wilcoxon test obtained p=0.000 (p<0.001). The Mann-Whitney test between groups I and II found p=0.284 (p>0.05). There was an effect of standard therapy and nerve mobilization on reducing ischilagia pain ec piriformis syndrome (p=0.00), there was an effect of standard therapy on reducing ischilagia pain ec piriformis syndrome (p=0.00), there was no difference in the effect between standard therapy and nerve mobilization with standard therapy alone in reducing ischialgia pain ec piriformis syndrome (p>0.05), standard therapy and nerve mobilization were as effective as standard therapy alone in reducing pain ischialgia ec piriformis syndrome. The conclusion of this study is standard therapy and nerve mobilization are as effective as standard therapy alone in reducing sciatic pain ec piriformis syndrome.